Spatially resolved Hα and ionizing photon production efficiency in the lensed galaxy MACS1149-JD1 at a redshift of 9.11 - Álvarez Márquez, Javier; Colina, L.; Gómez, A. Crespo; Rinaldi, P.; Melinder, J.; Östlin, G.; Annunziatella, M.; Labiano, A.; Bik, A.; Bosman, Sarah; Greve, T. R.; Wright, G.; et al. (Astronomy and astrophysics, 2024)
We present MIRI/JWST medium-resolution spectroscopy (MRS) and imaging (MIRIM) of the lensed galaxy MACS1149-JD1 at a redshift of z = 9.1092 ± 0.0002, when the Universe was about 530 Myr old. We detect, for the first time, spatially resolved Hα emission in a galaxy at a redshift above nine. The structure of the Hα emitting gas consists of two clumps, S and N, carrying about 60% and 40% of the total flux, respectively. The total Hα luminosity implies an instantaneous star-formation rate in the range of 3.2 ± 0.3 and 5.3 ± 0.4 M⊙ yr−1 for sub-solar and solar metallicities. The ionizing photon production efficiency, log(ζion), shows a spatially resolved structure with values of 25.55 ± 0.03; 25.47 ± 0.03; and 25.91 ± 0.09 Hz erg−1 for the integrated galaxy and clumps S and N, respectively. The Hα rest-frame equivalent width, EW0 (Hα), is 726−182+660 Å for the integrated galaxy, but it presents extreme values of 531−96+300 Å and ≥1951 Å for clumps S and N, respectively. The spatially resolved ionizing photon production efficiency is within the range of values measured in galaxies at a redshift above six and well above the canonical value (25.2 ± 0.1 Hz erg−1). The EW0 (Hα) is a factor of two lower than the predicted value at z = 9.11 based on the extrapolation of the evolution of the EW0 (Hα) with redshifts, ∝(1 + z)2.1, including galaxies detected with JWST. The extreme difference of the EW0 (Hα) for clumps S and N indicates the presence of a recent (< 5 Myr) stellar burst in clump N and a star formation over a larger period of time (e.g., ∼50 Myr) in clump S. The different ages of the stellar population place MACS1149-JD1 and clumps N and S at different locations in the log(ζion) to EW0 (Hα) plane and above the main relation defined from intermediate- and high-redshift (z = 3 − 7) galaxies detected with JWST. Finally, clump S and N show very different Hα kinematics, with velocity dispersions of 56 ± 4 km s−1 and 113 ± 33 km s−1, likely indicating the presence of outflows or increased turbulence in clump N. The dynamical mass Mdyn = (2.4 ± 0.5) × 109 M⊙, obtained from the size of the integrated Hα ionized nebulae and its velocity dispersion, is within the range previously measured with the spatially resolved [OIII]88 μm line.
Online veröffentlicht: 31. Mai 2024
Gesehen am 17.02.2025